2019
DOI: 10.1002/1348-9585.12088
|View full text |Cite
|
Sign up to set email alerts
|

Health status of workers approximately 60 years of age and the risk of early death after compulsory retirement: A cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There were 12 studies [47][48][49][50][51][52][53][54][55][56][57][58] (13 cohorts; 187,866 participants) with general populations (Table S3). Of these, seven cohorts were in East Asia, and three cohorts in each Europe and North America.…”
Section: General Populationsmentioning
confidence: 99%
“…There were 12 studies [47][48][49][50][51][52][53][54][55][56][57][58] (13 cohorts; 187,866 participants) with general populations (Table S3). Of these, seven cohorts were in East Asia, and three cohorts in each Europe and North America.…”
Section: General Populationsmentioning
confidence: 99%
“…Additionally, other potential risk factors like the psychosocial work environment ( Watanabe et al, 2018 ) and occupational physical activity ( Brighenti-Zogg et al, 2016 ) should be investigated over the working life-course and among older workers. MetS has been related to early death after retirement ( Sakurai et al, 2020 ) and possibly lower quality of life in retirement due to MetS related consequences like CVD and T2DM ( Laiteerapong et al, 2011 ; Schofield et al, 2012 ), thus it is important to examine the effect of the retirement transition on MetS and its components. It is currently unclear how the retirement transition influences objective health outcomes like MetS ( Xue, Head, & McMunn, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to investigate MetS and the individual MetS components among older workers as MetS related consequences like CVD and T2DM are related to an increased risk for early work exit and disability benefits ( Kouwenhoven-Pasmooij, Burdorf, Roos-Hesselink, Hunink, & Robroek, 2016 ). Further, the number of MetS components at the age of 60 is significantly associated with early death after retirement ( Sakurai et al, 2020 ) and the quality of life in retirement can be affected by CVD and T2DM ( Laiteerapong et al, 2011 ; Schofield et al, 2012 ). A recent literature review reported that most studies about MetS among workers are cross-sectional and focus on the general working population ( Santana, das Merces, Magalhães, Costa, & D’Oliveira, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 17 Moreover, a higher number of MetS components at the age of 60 is associated with early death after retirement. 18 To date, only a few studies have investigated the effect of employment transition type on MetS incidence among older workers. 12 Two longitudinal studies investigated MetS incidence after transitioning from employment to retirement and unemployment, and another two longitudinal studies examined the effect of retirement on metabolic biomarkers.…”
Section: Original Researchmentioning
confidence: 99%